Adaptation of Community-Based Tourism Enterprise for New Normal in Samut Songkhram Province - Ninaroon, Panida; Boonying, Jiraporn (Journal of Thai Hospitality and Tourism, 2023)
This article presents the findings from the synthetic sub-project, including 1) the study of the potential of community-based tourism for new normal tourism; 2) the model adaptation behavior of community-based tourists; and 3) the evaluation of community-based tourism standards for new normal tourism, which is based on the adaptation of community-based tourism for the new normal project in Samut Songkhram province. The results revealed that 1) the adaptation of entrepreneurs by the distribution channels is at a high level; 2) the model adaptation behavior of tourists minimizes traveling distances; hygiene and safety were the most important; and 3) the potential of hygiene in micro-enterprise is at the highest level by places for tourists and community.